Tinjauan Yuridis Wanprestasi dalam Perjanjian Pemborongan Kerja Horizontal Directional Drilling (Hdd) di Kabupaten Gresik - Amany M A; Lintang Yudhantaka (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The binding of the parties to the construction service business is contained in the construction work contract. The construction work contract contains an agreement between the employer and the executor, which generally discusses rights and obligations. The purpose of this study is to find out how the form and content of the cooperation agreement between CV. X and PT. Cipta Wisesa Bersama, as well as find out the efforts to resolve defaults that occurred between CV. X and PT. Cipta Wisesa Bersama. The results of this study can be concluded that the cause of default is CV. X did not pay the money for the completion of the work to PT. Cipta Wisesa Bersama.